Utilization of palm oil fuel ash in concrete: a review - Safiuddin, M.; Salam, M.A.; Jumaat, Mohd Zamin (Journal of Civil Engineering and Management, 2011)
Uncontrolled dumping of palm oil fuel ash (POFA) not only occupies valuable land but also creates environmental pollution and health hazard. These problems can be reduced to large extent by using POFA in concrete. A number of research works have been carried out to investigate the potential of POFA for use as a supplementary cementing material in normal, high strength, high performance, and aerated concretes. This paper presents a review on the use of POFA in different types of concrete. It firstly discusses the physical and chemical properties of POFA. Then the emphasis has been given on the effects of POFA on the fresh and hardened properties, and durability of concrete. This paper shows that both ground and unground POFA increase the water demand and thus decrease the workability of concrete. However, ground POFA has shown a good potential for improving the hardened properties and durability of concrete due to its satisfactory micro-filling ability and pozzolanic activity. In addition to discussing the benefits of POFA, this study has identified certain gaps in the present state of knowledge on POFA concrete, and listed several research needs for future investigation. The findings of this study would encourage the use of POFA as a supplementary cementing material for concrete.